Administration of ketamine for unipolar and bipolar depression. (2nd January 2017) - Kraus, Christoph; Rabl, Ulrich; Vanicek, Thomas; Carlberg, Laura; Popovic, Ana; Spies, Marie; Bartova, Lucie; Gryglewski, Gregor; Papageorgiou, Konstantinos; Lanzenberger, Rupert; Willeit, Matthäus; Winkler, Dietmar; et al.
Abstract: Objective: Clinical trials demonstrated that ketamine exhibits rapid antidepressant efficacy when administered in subanaesthetic dosages. We reviewed currently available literature investigating efficacy, response rates and safety profile. Methods: Twelve studies investigating unipolar, seven on bipolar depression were included after search in medline, scopus and web of science. Results: Randomized, placebo-controlled or open-label trials reported antidepressant response rates after 24 h on primary outcome measures at 61%. The average reduction of Hamilton Depression Rating Scale (HAM-D) was 10.9 points, Beck Depression Inventory (BDI) 15.7 points and Montgomery-Asberg Depression Rating Scale (MADRS) 20.8 points. Ketamine was always superior to placebo. Most common side effects were dizziness, blurred vision, restlessness, nausea/vomiting and headache, which were all reversible. Relapse rates ranged between 60% and 92%. To provide best practice-based information to patients, a consent-form for application and modification in local language is included. Conclusions: Ketamine constitutes a novel, rapid and efficacious treatment option for patients suffering from treatment resistant depression and exhibits rapid and significant anti-suicidal effects. New administration routes might serve as alternative to intravenous regimes for potential usage in outpatient settings. However, long-term side effects are not known and short duration of antidepressant response need ways to prolong ketamine's efficacy.